1984
DOI: 10.1002/j.1460-2075.1984.tb02260.x
|View full text |Cite
|
Sign up to set email alerts
|

A putative primer for second-strand DNA synthesis of maize streak virus is virion-associated.

Abstract: We have isolated, from maize streak virus (MSV) preparations, a population of ‘nested’ DNA molecules. These molecules have ribonucleotides covalently linked to the DNA species’ discrete 5′ deoxyribonucleotide terminus. The major species has a DNA sequence of 80 nucleotides which is complementary to a region 5′ of two hairpin structures on the MSV genome, almost exclusively in an intergenic region. These molecules have been used to prime the synthesis in vitro of a complementary strand to virion DNA, initiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…In addition, (31). This 3' end mapped 9bp from the 3' end of the major species of "primer-like" DNA molecules found on virion DNA (34). A polypeptide of 28,000 MW was mapped, by hybrid-arrested translation, to the region coding for the two-virion sense transcripts on MSV DNA (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, (31). This 3' end mapped 9bp from the 3' end of the major species of "primer-like" DNA molecules found on virion DNA (34). A polypeptide of 28,000 MW was mapped, by hybrid-arrested translation, to the region coding for the two-virion sense transcripts on MSV DNA (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…First, the monocot-type DNAs have two non-coding (intcrgenic) regions, whereas dicot-type DNAs have only one intergenic region in DNA 1. Second, the monocot-type viruses have small (approximately 80 nucleotides) complementary-strand DNAs which contain a few covalently bound, 5'-terminal ribonucleotides and are associated with and probably base-paired to viral DNA inside nucleocapsids (Howell, 1984;Donson et al, 1984Donson et al, , 1987Andersen et al, 1988;Hayes et al, 1988;Lazarowitz, 1988). These small DNAs are thought to be primers of complementary strand DNA synthesis.…”
Section: Comparison Of Coat Proteinsmentioning
confidence: 99%
“…It is likely that complementarysense DNA synthesis on this replicative intermediate proceeds by a similar mechanism to that on ssDNA following uncoating. The encapsidated viral DNA of geminiviruses that infect monocotyledonous plants is predominantly single-stranded but is associated with a complementary-sense DNA fragment of approximately 80 nucleotides containing 5' terminal ribonucleotides [6][7][8][9]. The ability to synthesise full-length dsDNA in vitro using viral DNA extracted from purified virus particles suggested that the fragment might serve as a primer for at least the first round of DNA synthesis in vivo.…”
Section: Introductionmentioning
confidence: 99%